Emission factors of CO2, CO and CH4 from Sumatran peatland fires in 2013 based on shipboard measurements. Issue 1 (1st January 2017) - Nara, Hideki; Tanimoto, Hiroshi; Tohjima, Yasunori; Mukai, Hitoshi; Nojiri, Yukihiro; Machida, Toshinobu
Abstract: We observed prominent CO enhancements with simultaneous enhancements of CO2 and CH4 around the Malay Peninsula in South-East Asia from mid-June to mid-August 2013 based on systematic shipboard observations. We identified 18 episodes of CO enhancement during the period, which were responsible for the largest positive anomaly of CO observed in the areas of off the eastern coast of Peninsular Malaysia and in the Straits of Malacca between 2007 and 2013 based on shipboard observations. Satellite data revealed that the CO enhancements resulted mainly from the emissions from large-scale biomass burning in north-central Sumatra. We characterized five biomass burning peaks with strong fire emission signatures based on the relationship between CO2 and CO. From these peaks, we estimated the average emission factors (EFs) for CO2, CO and CH4 from the fires in the study area. The estimated average EFs for CO2 and CO agreed well with those predicted by version 4.1s of the Global Fire Emissions Database (GFED4.1s) using the recommended EF values, but the CH4 EF differed substantially, suggesting high uncertainty of the CH4 EF for peat in GFED4.1s. We estimated the typical EF values for peat fires based on the average EF values from the present study. The estimated typical EF values were 1663 ± 54 g/kg for CO2, 205 ± 23 g/kg for CO and 7.6 ± 1.6 g/kg for CH4 . Despite the lack of a clear difference for CO2 and CO, our estimated typical EF of CH4 was less than half of the GFED4.1s-recommended EF and was comparable to previously reported EF values for Borneo peat. These results suggest a significant overestimation of the EF of CH4 for peat fires in GFED4.1s; using the present values would greatly decrease the estimated contribution of Equatorial Asia to global fire emissions of CH4, especially in drought years.